Target-Oriented Risk Assessment of AFB1 in Buckwheat Consumed in Armenia - Stepanyan, S. A.; Pipoyan, D. A.; Beglaryan, M. R. (ՀԱԱՀ հիմնադրամ)
Cereals, including buckwheat are consumed as an essential source of energy, minerals, fiber, and vitamins. However, these products are susceptible to aflatoxin B1 (AFB1) infection from various fungi. Considering the wide consumption of buckwheat in Armenia, this study aims to assess the dietary exposure of AFB1 to Armenian adult population. 24-hour recall method was used to evaluate buckwheat consumption. While AFB1 contents do not exceed the maximum residue levels, dietary exposure estimates exceed the toxicological reference value for females residing in Tavush region, as well as for consumers of cluster 2 (buckwheat consumption of 64.59 g/day). Hence, the consumption of buckwheat alone has the potential to cause adverse health effects.
Keywords: Food Science and Technology